DEVELOPING TRAINING MANAGEMENT MODEL OF ENTERPRENURSHIP LEARNING BASED ON PRODUCTION UNIT TOWARD VOCATIONAL HIGH SCHOOL TEACHERS (Universitas Negeri Semarang, 2014)
The study aims to: describe the design of the training model, obtain the experimental results of the model, and investigate the effectiveness of the training model. This study employs the approach of Research and Development (R&D). The stages are: undergoing a preliminary study, setting up the empirical models based on the results of the preliminary analysis, drafting the hypothetical model based on the empirical models, designing validation by some experts, improving the model design, testing the effectiveness of hypothetical models, refining the hypothetical model into a finding model. The data are collected through observation, interview, questionnaire, and documentation. The descriptive data are analyzed qualitatively and analytically, using a paired t-test at a significance level of 5%. The model is equipped with a manual book of management training as its outcome product. The hypothetical model validation results show: the model performs very high effectiveness toward the mean score of teachers’ ability in designing entrepreneurship learning based on production unit after the application of the model at the score of 4.89 and before the application of the model at 1.36. The t value = 36,085> t table = 2.776 at 0.05 significance level, the difference of mean scores of instructional practices in schools for trained and untrained teachers at SMK 1 Jepara is at 4.83 and 1.83; SMK Kedung is at 4.83 and 1.50; SMK Kalinyamatan is at 4.67 and 1.67; SMK Pakis Aji is at 4.83 and 1.67, and SMK Muhammadiyah Keling is at 4.33 and 1.50. The evaluation results of the hypothetical model effectiveness based on its mean score is at 4.26 (very high) over 13 indicators. The study concludes that the training model of entrepreneurship learning based on production unit is effective to improve the quality of teachers in teaching entrepreneurship.